The Influence of Democratic Leadership on Employee Performance With Psychological Empowerment as a Mediation Variable in the Women's Empowerment Office, the Protection of Children and Community (Dp3am) Binjai City - Muhammad Arif Pohan; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of Democratic Leadership on Employee Performance mediated by Psychological Empowerment in Employees of the Women's Empowerment, Child Protection and Community Service (DP3AM) of Binjai City. This research was carried out at the Women's Empowerment, Child Protection and Community Protection Office (DP3AM) of Binjai City. The type of research is quantitative associative. The sample in this study is 61 employees of the Women's Empowerment, Child Protection and Community Service (DP3AM) of Binjai City. The sampling technique in this study uses a saturated sample so that the entire population will be a sample of 61 people. The results of the study show that Democratic Leadership has a significant influence on Employee Performance as shown by a T-Statistic value of 9,023 > 1.96 and a P Value of 0.001 < 0.05. In the influence of Democratic Leadership on Psychological Empowerment, data obtained T-Statistical values were obtained from 10,966 > 1.96 and P-Value values of 0.000 < 0.05 or no influence of Democratic Leadership on Psychological Empowerment. Psychological Empowerment has a significant effect on Employee Performance with a T-Statistic value of 16,939 > 1.96 with a P-Value of 0.000 < 0.05. In the indirect influence, the results show that Psychological Empowerment also has a role as an intervening variable that will explain the relationship between Democratic Leadership and the Performance of Employees of the Women's Empowerment, Child and Community Protection Office (DP3AM) of Binjai City. This shows that improvements in Democratic Leadership will be able to increase Psychological Empowerment, which in turn can also contribute to improving the Performance of Employees of the Women's Empowerment, Child and Community Protection Office (DP3AM) of Binjai City.